KOMPARASI AKSES PUPUK BERSUBSIDI MENGGUNAKAN KARTU TANI DENGAN APLIKASI I-PUBERS - Siti Rukmana; Farida Mardhatilla; Dwi Purnomo Purnomo (Universitas Garut, 2026)
Food security is one of the main priorities of national development, implemented through fertilizer subsidy policies for farmers. To improve transparency and efficiency in the distribution of subsidized fertilizers in accordance with the 6T principles (right type, quantity, price, time, place, and target), the government has introduced two distribution instruments, namely the Farmer Card (Kartu Tani) and the i-Pubers Application. This study aims to analyze the effect of the Farmer Card and the i-Pubers Application on access to subsidized fertilizers and to compare the effectiveness of both instruments. The research was conducted in Rungkang Village, Losari District, Brebes Regency, using a quantitative descriptive-comparative approach. The sample consisted of 87 respondents, including 47 Farmer Card users and 40 i-Pubers Application users. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, simple linear regression, F-test, t-test, and independent sample t-test. The results indicate that both instruments have a significant effect on access to subsidized fertilizers, although with different levels of effectiveness. The independent sample t-test reveals a significant difference between the two groups, where the average access score of i-Pubers Application users (47.3) is higher than that of Farmer Card users (44.0). These findings suggest that the i-Pubers Application is more effective in supporting access to subsidized fertilizers due to faster verification processes and fewer technical constraints.